Body image and body composition: Comparisons of young elite soccer players and controls - Arroyo, M.; Gonzalez-de-Suso, J. M.; Sanchez, C.; Ansotegui, L.; Rocandio, A. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
The purpose of this study was to evaluate body composition and body image (perception and satisfaction) in a group of young elite soccer players and to compare the data with those of a control group (age and BMI matched). Participants were 56 volunteer males whose mean age and BMI were 19.6 (SD 1.3) years and 23.3 (SD 1.1) kg/m2, respectively. Results showed that soccer players have a higher lean mass and lower fat mass than controls. Moreover, body perception (difference between current and actual image) was more accurate in controls than in soccer players, and the results suggest a tendency for soccer players to aspire to have more muscle mass and body fat. Soccer players perceived an ideal image with significantly higher body-fat percentage than their current and actual images. There were no body-dissatisfaction differences between groups, however. Although the results are necessarily limited by the small sample size, the findings should be of interest to coaches of young elite soccer teams.